Mengelola Sampah Plastik, Langkah Kecil Menuju Lingkungan yang Lebih Bersih - Aziva Umairoh; Solfema Solfema; Lili Dasa Putri (Universitas Palangka Raya, 2025)
One of the biggest environmental problems in the world today is plastic waste. The accumulation of plastic that is difficult to decompose endangers human health and land and marine ecosystems. This is why managing plastic waste is an important small step towards making the environment cleaner and more sustainable. Reducing the use of single-use plastics, implementing recycling, and developing new ways to use used plastics for valuable products. Additionally, there was a discussion about how individual awareness, community collaboration, and government support are essential for plastic waste management. To reduce the negative effects of plastic waste, society can help future generations live better lives by implementing simple but consistent actions.